Helminth eggs die-off and nutrients: Human excreta storage experiment - Vu Van Tu; Phuc Pham Duc; Hung Nguyen-Viet; Zurbrugg, C.; Huu Bich, T.; Zinsstag, Jakob (2013)
Are the current practices of handling human excreta for agricultural purposes by farmers in Vietnam good enough?This study set up an excreta storage experiment to research how to inactivate Ascaris lumbricoides eggs and stillmaintain the nutrient value of human excreta.